Országmárkázástól a versenyképes identitásig - és még tovább. A country branding megjelenése, céljai és természete 2009-ben és 2017- ben - Papp-Váry, Árpád Ferenc (Marketing & Menedzsment, 2017)
It is not accidental that countries take over the conventional brand management techniques, because 51 from the 100 strongest economies of the world are companies, not countries. Besides, the number of countries (we might say „competitors”) has increased significantly. While the United Nations had 51 members in 1945, it has 192 in 2009. In the light of the previously mentioned, the primary goals of country branding are economic. The three major components of 'sale' are as follows: 1. The attraction of tourists, 2. The stimulation of incoming investments, 3. The boost of export. It is imperative to point out that a good country brand can also have other additional effects: 4. Bigger role in international organisations and foreign affairs, 5. The bettering of the citizens’ general feeling. • Although country branding is a new field there are numerous lessons, including: • A country brand is multidimensional. Not only because it consists of more dimensions than a classical brand but because for the different target groups other things can be important from these. • In the case of countries, the number of consumer touch points is much higher and most of them can be controlled only with difficulties. • A comprehensive branding programme has to be accepted in the given country at first (by the media, the business sphere and the people respectively) a brand outwards can be built only after this. • Country building and country image building have to happen at the same time, in fact, the previous one anticipates the latter one to some extent. Country branding and country rebranding are long-term processes. Their results are likely to be seen only after having 15-20 years passed.